Factors influencing the length of hospital stay of people experiencing homelessness - Karpenko, Renate; Lech, Sonia; Schenk, Liane; Schindel, Daniel (Frontiers in Public Health, 2025)
IntroductionPeople experiencing homelessness (PEH) are affected by poor mental and physical health. Crucial healthcare remains inaccessible. In urgent need, people seek assistance in hospitals. The length of stay (LOS) can be used as an indicator of quality in inpatient healthcare. This study aimed to reveal factors influencing the LOS of PEH.MethodsA retrospective secondary data analysis of hospital discharge letters was conducted. Descriptive analyses were used to examine sociodemographics and the LOS in relation to individual disease groups according to the ICD-10. Disease burden was evaluated using a modified Elixhauser Comorbidity Score (ECS). Analyses were conducted separately by sex. Multiple linear regression was used to identify factors influencing the LOS.ResultsThe analysis included 807 hospital discharge letters from 521 PEH. The majority of letters were from men (89.2%). Both groups differed significantly in terms of age, with more women under the age of 30 years (27.1% versus 10.3%, p < 0.001). The total median LOS was 7 days with no sex difference (IQR women: 3.5–11.5, IQR men: 3–12, p = 0.837). Women had the longest median LOS for infectious diseases, skin diseases, and mental disorders. Men had the longest median LOS for infectious diseases, musculoskeletal diseases, and respiratory diseases. The median ECS was zero for both (p = 0.548). Significant factors influencing the LOS included mental disorders (β: 0.327, B: 0.788, CI(B): 0.465–1.110, p < 0.001), infectious diseases (β: 0.240, B: 0.869, CI(B): 0.504–1.234, p < 0.001), and homelessness duration (β: 0.213, B: 0.059, CI(B): 0.031–0.086, p < 0.001).ConclusionGender had no significant effect on the LOS. The significant demographic factor was the duration of homelessness, indicating that the health status of PEH deteriorates and access to healthcare decreases over time. Medical factors had a strong influence on the LOS of PEH. In highly prevalent disease categories, PEH have long hospital stays. A relevant factor for the LOS of PEH is their health status. Improving care structures has the potential to improve the LOS. Early integration of healthcare and social work can ensure a safe discharge and influence the LOS. The development of adequate aftercare services for PEH is necessary.